Carbon Tetrachloride-Induced Testicular Toxicity and Histopathological Alteration in Male Swiss Albino Mice - Habiba Eljaafari; Zainab EL Mabrouk; Fauzia Mohamed; Hanin Tunsi; Samira Musa Sasi (AlQalam Journal of Medical and Applied Sciences, 2024)
Recently there has been an increased association between toxic substances present in the environment and male infertility. Carbon tetrachloride (CCL4) is widely used as a chemical intermediate and as a feedstock in the production of chlorofluorocarbons. CCL4 is highly toxic to the liver, kidney, testicle, brain and other tissues. Therefore, the present study was designed to identify its effect on the reproductive system in adult male mice. Thirty adult male albino mice were divided into three equal groups (n=10): the first group control, the second group received 0.1m/100g body weight olive oil and the third group received 0.1ml/100g/body weight CCL4 intraperitoneally every alternate day for three weeks. The results showed that CCl4 causes a significant decrease in body weight, sperm motility, sperm count and testosterone level, while it leads to a significant increase in the number of abnormal sperm morphology. Additionally, CCL4 caused apparent alterations in the histological structure of the testes. In conclusion, CCl4-induced reproductive toxicity in male mice. في الآونة الأخيرة، كان هناك ارتباط متزايد بين المواد السامة الموجودة في البيئة والعقم عند الرجال. يستخدم رابع كلوريد الكربون (CCL4) على نطاق واسع كمادة كيميائية وسيطة وكمادة وسيطة في إنتاج مركبات الكربون الكلورية فلورية. CCL4 شديد السمية للكبد والكلى والخصية والدماغ والأنسجة الأخرى. ولذلك صممت الدراسة الحالية للتعرف على تأثيره على الجهاز التناسلي لدى ذكور الفئران البالغة. تم تقسيم ثلاثين فأرًا أبيضًا بالغًا من الذكور إلى ثلاث مجموعات متساوية (العدد = 10): المجموعة الأولى السيطرة، والمجموعة الثانية تلقت 0.1 م / 100 جم من وزن الجسم زيت الزيتون والمجموعة الثالثة تلقت 0.1 مل / 100 جم / وزن الجسم من CCL4 داخل الصفاق كل بديل. يوم لمدة ثلاثة أسابيع. أظهرت النتائج أن CCl4 يسبب انخفاضا ملحوظا في وزن الجسم وحركة الحيوانات المنوية وعدد الحيوانات المنوية ومستوى هرمون التستوستيرون، في حين يؤدي إلى زيادة كبيرة في عدد الأشكال غير الطبيعية للحيوانات المنوية. بالإضافة إلى ذلك، تسبب CCL4 في حدوث تغييرات واضحة في البنية النسيجية للخصيتين. في الختام، السمية الإنجابية الناجمة عن CCl4 في ذكور الفئران